PENGEMBANGAN USAHA KRIPIK SINGKONG DI DUSUN LURING DESA SUKOPURO KECAMATAN JABUNG KABUPATEN MALANG - Rokhmawati, Dian; Yuliana, Rachma (Nindikayla Institute, 2023)
Luring Hamlet is a hamlet located in the village of Sukopuro Jabung. The Sukopuro village area includes 4 hamlets namely Luring, Karang Rejo, Kepuh and Pandan Rejo. The total area of Sukopuro village is 630,935 hectares. With an area of approximately 150 hectares, Luring hamlet includes hamlets that have a fairly large agricultural land, which is 120 hectares. Wetlands produce vegetables and sweet potatoes, while drylands produce sugarcane, cassava, maize and durian. The superior commodity is cassava. The resident's home-based business is the production of cassava chips. Unfortunately, this business has not run optimally. One of the businesses that became the location of assistance from the service team was the cassava chip business owned by Pak Rahmat's family. Traditional business management causes low productivity. To start business development, the service team provides direction to change the products sold from previously in the form of raw chips to chips as ready-to-consume snacks with hygienic, durable and durable packaging. In addition, the service team also provides directions so that in the production process fixed procedures or SOPs are carried out starting from simple ones to maintain product hygiene such as arranging the location for drying chips, using goring oil in a healthy manner and packaging of chips that are hygienic, safe and durable.